Factors on the accrual accounting adoption: Empirical evidence from Indonesia - Khoirul Aswar (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: This study aims to examine the relationship between top management support, implementation costs, and effective project leader and the level of accrual accounting adoption in Indonesia's municipalities. Design/methodology/approach: The hypotheses of the study were tested using the survey data from 220 municipalites in Indonesia. The instrument for content and construct validity and reliability was tested. Then, the hypotheses were tested using Structure Equation Modelling (SEM) by SmartPLS. Finding: This study found that, top management support and implementation cost have significant relationship with the level of accrual accounting adoption. Meanwhile, effective project leader has no significant relationship with the level of accrual accounting adoption. Research limitations/implications: This study contributions to provide input into the adoption of Government Regulation No. 71 of 2010 in order to apply the rule of accrual accounting to the fullest, and to minimize errors in financial reporting with the identification of possible obstacles faced in implementing accrual accounting. This study recommended that, more factors such as human resources, external audit are needed to complement and improve financial reporting with accrual accounting adoption. Originality/value: To the best of the researcher's knowledge, no study of Indonesian municipalities has tested the impact of factor such as top management support, implementation cost, and effective project leader on the level of accrual accounting adoption.
Keywords: I28; M15; M48; M53; 330; Accrual Accounting Adoption; Government Regulation; Factors; Indonesia